Serum Concentrations of Organochlorine Pesticides in Non-Vocationally Exposed Population of Harbin City, China - Sun, Guo-Xin; Liu, Li-Yan; Wang, De-Cai; Xie, Fang-Qin; Wang, Shao-Ling; Li, Ying; Chen, Yan-Feng; Sun, Chang-Hao (Asian Journal of Chemistry, 2010)
This work reports the method for determining organochlorine pesticides in human serum and evaluate the accumulation level of organochlorine pesticides in non-vocationally exposed residents lived at Harbin city, P.R. China. The blood samples were treated with ultrasonic, purified by C18 solid phase extraction column and tested with the capillary columns gas chromatograph equipped with ECD detector. The recovery of ten kinds of organochlorine pesticides in human serum were 84.2-92.1 %. The relative standard deviation of the method was 2.61-14.4 %, linearity range at 0.2-50.0 μg/L. The range of detection limit were 0.02-0.05 ng/ mL and the correlation coefficient were r > 0.999. Of the 220 people investigated, 60 % were detected with different serum levels of organochlorine pesticides (range: 0.012-32.107 μg/L). The detection rate was 58.1 and 61.7 % in male and female, respectively. The serum level of accumulated organochlorine pesticides of non-vocationally exposed residents in Harbin were higher in female than that in male. However, both of them are in lower level of accumulated organochlorine pesticides.